Transgenerational hypocortisolism and behavioral disruption are induced by the antidepressant fluoxetine in male zebrafish Danio rerio - Vera-Chang, Marilyn N.; St-Jacques, Antony D.; Gagné, Rémi; Martyniuk, Chris J.; Yauk, Carole L.; Moon, Thomas W.; Trudeau, Vance L. (Proceedings of the National Academy of Sciences - PNAS, 2018)
The global prevalence of depression is high during childbearing. Due to the associated risks to the mother and baby, the selective serotonin reuptake inhibitor fluoxetine (FLX) is often the first line of treatment. Given that FLX readily crosses the placenta, a fetus may be susceptible to the disruptive effects of FLX during this highly plastic stage of development. Here, we demonstrate that a 6-day FLX exposure to a fetus-relevant concentration at a critical developmental stage suppresses cortisol levels in the adult zebrafish (F₀). This effect persists for three consecutive generations in the unexposed descendants (F₁ to F₃) without diminution and is more pronounced in males. We also show that the in vivo cortisol response of the interrenal (fish “adrenal”) to an i.p. injection of adrenocorticotropic hormone was also reduced in the males from the F₀ and F₃ FLX lineages. Transcriptomic profiling of the whole kidney containing the interrenal cells revealed that early FLX exposure significantly modified numerous pathways closely associated with cortisol synthesis in the male adults from the F₀ and F₃ generations. We also show that the low cortisol levels are linked to significantly reduced exploratory behaviors in adult males from the F₀ to F₂ FLX lineages. This may be a cause for concern given the high prescription rates of FLX to pregnant women and the potential long-term negative impacts on humans exposed to these therapeutic drugs.